(6x-5)=(8x-50)

Simple and best practice solution for (6x-5)=(8x-50) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-5)=(8x-50) equation:



(6x-5)=(8x-50)
We move all terms to the left:
(6x-5)-((8x-50))=0
We get rid of parentheses
6x-((8x-50))-5=0
We calculate terms in parentheses: -((8x-50)), so:
(8x-50)
We get rid of parentheses
8x-50
Back to the equation:
-(8x-50)
We get rid of parentheses
6x-8x+50-5=0
We add all the numbers together, and all the variables
-2x+45=0
We move all terms containing x to the left, all other terms to the right
-2x=-45
x=-45/-2
x=22+1/2

See similar equations:

| 19+3x-8x=x-42 | | 3x+7+2x+5=67 | | 0.6+3=0.1r-7 | | -u/3=10 | | 0.7x-2.9=2.5x+2.4 | | 3,8g=-104.12 | | 1/4(8x-12)=-3 | | s(s+3)=28 | | 3a+5=-5 | | -5b+10=-3b-8 | | 53x=8 | | X+29=2x+30+10 | | n=-9-2n | | 3b-18=5 | | 18x+16=20x+2 | | 2z-6=1 | | 3z+12=5 | | 6=11-10/x | | 5v+6=-6-7v | | 3a,a+2,2a-1,3a+6=4 | | 90+(5x+11)+(3x+7)=180 | | 2x+1x+-2=(2x+-2+-1) | | X÷2=x-24 | | 3y-9=4 | | 8m-6m^2=0 | | -2p=-3p-2 | | -5+15/k=0 | | 3a-15=2 | | 2n-6/6+3n=6 | | 2/3(8x+12)=12 | | b-6.25=-13.5 | | -86+45=x |

Equations solver categories